A Peptide Analogue of Selectin Ligands Attenuated Atherosclerosis by Inhibiting Monocyte Activation. (6th May 2019) - Ye, Zhishuai; Zhang, Shanfeng; Liu, Yubo; Wang, Shujing; Zhang, Jianing; Huang, Rongchong
Abstract : Background . Circulating monocytes play a critical role in the pathogenesis of atherosclerosis. Monocyte homing to sites of atherosclerosis is primarily initiated by selectin. Thus, blockade of the interaction of selectins and their ligands holds a significant role in monocyte homing which might be a potential approach to treat atherosclerosis. Here, we investigated the efficacy of a novel peptide analogue of selectin ligands IELLQAR in atherosclerosis. Methods and Results . In this study, we firstly measured the effect of the IELLQAR selectin-binding peptide on the inhibition of binding of selectins to monocytes by flow cytometry, which exhibited a dose-dependent inhibitory effect on the binding of the P-, E-, and L-selectins to monocytes, especially the inhibition of P-selectin binding to human peripheral blood monocytes (PBMCs) (half maximal inhibitory concentration (IC50 5 μ M)) and THP-1 cells (IC50 10 μ M). Furthermore, IELLQAR inhibited P-selectin-induced activation of CD11b on the surface of monocytes and decreased adhesion of monocytes to the endothelium . ApoE -/- mice with or without IELLQAR (1 or 3 mg/kg) fed a Western-type diet (WTD) or which had disturbed blood flow-induced shear stress underwent partial left carotid artery ligation (PLCA) to induce atherosclerosis. In the WTD- and PLCA-induced atherosclerosis models, atherosclerotic plaque formation and monocyte/macrophage infiltration of the arterial wall both decreased in ApoE -/- mice treated with the IELLQAR peptide. Our results also revealed that IELLQAR inhibited the differentiation of monocytes into macrophages through P-selectin-dependent activation of the nuclear factor- (NF-) κ B and mammalian target of rapamycin (mTOR) pathways. Conclusion . Collectively, our results demonstrated that IELLQAR, a peptide analogue of selectin ligands, inhibited selectin binding to monocytes, which led to subsequent attenuation of atherosclerosis via inhibition of monocyte activation. Hence, use of the IELLQAR peptide provides a new approach and represents a promising candidate for the treatment of atherosclerosis in the early stage of disease.